Genome-Wide Detection of Predicted Non-coding RNAs Related to the Adhesion Process in Vibrio alginolyticus Using High-Throughput Sequencing - Huang, Lixing; Hu, Jiao; Su, Yongquan; Qin, Yingxue; Kong, Wendi; Zhao, Lingmin; Ma, Ying; Xu, Xiaojin; Lin, Mao; Zheng, Jiang; Yan, Qingpi (Frontiers in Microbiology, 2016)
The ability to adhere to fish mucus can be affected by environmental conditions and is considered to be a key virulence factor of Vibrio alginolyticus. However, the molecular mechanism underlying this ability is unclear. Our previous study showed that stress conditions such as exposure to Cu, Pb, Hg and low pH were capable of reducing the adhesion ability of V. alginolyticus. Non-coding RNAs (ncRNAs) play a crucial role in the intricate regulation of bacterial gene expression, thereby affecting bacterial pathogenicity. Therefore, we hypothesized that ncRNAs played a key role in the V. Alginolyticus adhesion process. To validate this, we combined high throughput sequencing with computational techniques to detect ncRNA dynamics in the stressed samples. The expression of randomly selected novel ncRNAs was confirmed by QPCR. Among the significantly changed ncRNAs, 30 ncRNAs were up-regulated and 2 ncRNAs were down-regulated by all stress treatments. The QPCR results reinforced the reliability of the sequencing data. Target prediction and KEGG pathway analysis indicated that these ncRNAs were closely related to pathways associated with in vitro adhesion. Our results indicated that the chemical stress-induced reduction in the adhesion ability of V. alginolyticus might be due to the perturbation of ncRNA expression. Our findings provide important information for further functional characterization of ncRNAs during the adhesion process of V. alginolyticus.